Determining factor Influencing customer retention of insurance products and services: A case of sixma group / Mohd Nazib Che Din, Mohamad Azmil Jamsari and Muhammad Luqman Sulaiman Azari - Che Din, Mohd Nazib; Jamsari, Mohamad Azmil; Sulaiman Azari, Muhammad Luqman (Arshad Ayub Graduate Business School, Universiti Teknologi MARA, 2018)
This study sets out to understand the variables influencing customer retention for a company that is involved in the insurance and Takaful services specifically, Sixma Group Sdn Bhd. The objectives of this study are to carry out the situational analysis for Sixma Group, to identify the factors that influence customer retention towards products and services and to recommend viable strategies for Sixma Group based on the findings of the study. The target respondents were those who do have insurance or Takaful policies in general and a total of 105 questionnaires were collected through a convenient sampling method. The data collected were interpreted by using four methods namely reliability test, descriptive analysis, Pearson correlation analysis and regression analysis. From the findings of this study, it was found that there is strong significant relationship between reputation with customer retention. The key findings in this study provide significant insights regarding the effects of price, service and reputation on customer retention in the insurance and Takaful industry. For future researchers, it is possible to replicate and compare this study in other service sectors such as banking and financial institutions